Inflammation: The Role of Different Mediators - Chhimwal, Jyoti; Sharma, Anu; Saini, Priyanka; Sharma, Shamiksha; Khan, Mohd. Shahid. (Asian Journal of Pharmaceutical Research and Development, 2015)
Inflammation is a protective response for the purpose of removal of exogenous and endogenous harmful substances produced by injurious stimuli and is a part of the healing process in wounded tissues. Since proinflammatory mediators such as COX-2, iNOS, tumor necrosis factor alpha (TNF-α), interleukin IL-1 and IL-6, proteases, and oxidants produced during the typical response can cause damage to normal tissues regardless of how and where the inflammatory response is triggered, the substances involved in the inflammatory response need to be tightly regulated. If the scavenging reaction is delayed, the inflammatory response may evolve into a variety of chronic inflammatory diseases, such as atherosclerosis, rheumatoid arthritis, asthma, and neurodegenerative diseases. A vast number of molecular studies have identified several target molecules involved in inflammatory changes, and most anti-inflammatory drugs currently used to suppress the biosynthesis of the inflammatory mediators mentioned earlier.